Synthesis and Characterization of a Silver Nanoparticles-Reduced Graphene Oxide Nanohybrid by using ‘Zingiber Officinale’ Extract as a Reducing and Stabilizing Agent - Izrini Ikhsan, Nurul; Farahah Jaffar, Nur (International Journal of Engineering and Technology, 2019)
An eco-friendly solution-based chemical approach has been used to prepare silver nanoparticles-reduced graphene oxide (AgNPs-rGO) nanohybrid using Zingiber officinale extract as a reducing and stabilizing agent. The products form a stable aqueous solution without any surfactant stabilizers and hence makes it possible to produce AgNPs-rGO nanohybrid on a large scale using low-cost solution processing technique. The nanohybrid was monitored at different concentration of GO solution (0.1 mg/ml, 0.5 mg/ml and 1.0 mg/ml) and characterized using UV- visible (UV-Vis) absorption spectrum, transmission electron microscopy (TEM), X-ray diffraction (XRD), and Raman spectroscopy analyses. From the UV-Vis analysis, the formation of silver nanoparticles (AgNPs) was confirmed and showed a surface plasmon resonance (SPR) absorption band at 420 nm for nanohybrids with GO concentration of 0.5 mg/ml. Raman spectra shows an increase in ID/IG ratio for rGO with values of 1.007 corresponding to the concentration of GO (0.5mg/ml) as compared to GO (0.88). Completely spherical Ag nanoparticles (NPs) were found at a nanohybrid with 0.5 mg/ml of GO with an average particle size of 20 nm. The AgNPs-rGO(0.5) nanohybrid exhibit fast electron-transfer kinetics for electrochemical reaction of Fe (CN)63-/4- redox couple, suggesting the potential applications for electrocatalysis and electrochemical sensor.